(untitled) (Nigerian Journal of Technology, 2018)
Learning is in form of continuous process that should translate to produce knowledge. The process of learning is very crucial in the fields of education and psychology which must be planned with appropriate strategy and approach. Several researchers have made many contributions to what could increase learners’ engagement in learning process that would lead to successfully learning outcome. Game technology in conjunction with learning have been attested as one of the ways that increase learners’ learning motivation and attention and have hands-on experience for effective learning performance. The conventional mode of learning mathematics as a subject seems abstract, tedious and dreadful to most students but with the deployment of game technology to learning would promote entertainment-education for constructive and cognitive knowledge processes. Hence, a digital game-based quadratic factorisation learning system is developed using the game theory of tic-tac-toe. The system is built on Microsoft.Net Framework and game logic. The system was subjected to a performance evaluation based on six criteria such as ease of use, intuitive user interface, correctness of results, usefulness of the system to problem solving, system speed of solving the problems and memory usage by the system. The results of the analysis demonstrated that the system is efficiently suitable for the underlined objectives. http://dx.doi.org/10.4314/njt.v37i2.23